Identification of a new species and three new records of Chaetomiaceae associated with commercial herbal teas in northern Thailand - Xu, Rong Ju; Huanraluek, Naruemon; Mapook, Ausana; Phukhamsakda, Chayanard; Boonmee, Saranyaphat (Phytotaxa, 2024)
This study aimed to identify fungi associated with commercial herbal teas from local markets in Chiang Rai and Chiang Mai, Thailand. A new species, Arcopilus albae was isolated from mulberry leaf tea and identified based on evidence from molecular phylogenetic analysis. Phylogenetic analysis of a combined ITS, LSU, TUB2, and RPB2 dataset indicated that the new species is a distinct taxon with high statistical support. Furthermore, two isolates of Canariomyces arenarium and three isolates of Chaetomium globosum are described as new host records from five different commercial herbal teas (black and red goji berries, chrysanthemum flower, mulberry leaf, and stevia leaf). One isolate of Ch. rectangulare is described as a new host record from black goji berry and a new geographical record from northern Thailand. This study provides additional collections of fungi associated with dried commercial herbal tea products from local markets in the North of Thailand.